Formação sobre ruínas : uma leitura da noção de experiência (Erfahrung) em Walter Benjamin - Nolli, Marcelo Ricardo (2021)
The aim of this dissertation is to investigate the notion of experience (Erfahrung) in the work of philosopher and cultural critic Walter Benjamin (1982-1940), seeking to articulate it to the field of Philosophy of Education. It is a hermeneutical and critical reading, taking as its central axis the concept of experience and looking to understand how it operates internally to the different phases of his thought. The premises of cultivation (Bildung) as a teleological and normatively closed conception are contested by his thought. That way, a different teleology is inferred, one that challenges Bildung and posits it in a new relationship to concepts such as temporality, history and narrative, despite not abandoning the wish-images contained in modernity. Among the main arguments developed here are: 1) We see a severe critique to modernity and to the Enlightenment (Aufklärung), without losing its dimensions related to cultivation—it is possible, then, to defend a dialectics of destruction-reconstruction; 2) Benjamin proposes an antievolutionist conception of history that pursuits the interruption of the course of progress, seeking to save the past and redeem it; 3) Experience in modernity is not possible because of the experience (Erlebnis) of the shock: what remains is redemption through remembrance (Eingedenken), aesthetics and a materialist pedagogy; 4) The telos of cultivation has no longer a defined form: this is the critique to the progressive dimension of history that negates childhood (therefore, we take the risk of situating an open teleology here, without a final end). 5) From critique (destructive moment) that converts into ruins (or saves) what is petrified in its mythical form, comes into play the child, who is capable of reconstituting the fragments and looking to another form of narration, another history and another temporality (constructive moment). That way, Benjamin’s work criticizes historicism and cultivation with a fixated end—that are convinced of the progressive advancement of Reason, History and Culture—when he presents himself as a thinker who renounces the closed teleological end, insofar as he privileges more singularity than totality, more the fragment than the complete reconstitution, more the possibilities of subversion of the present through the redemption of a past always close to being forgotten, than the nostalgic impulse of returning to an original moment when experience was still possible. Modernity appears here facing its impossibilities, its inconsistencies and failings, bringing us to a negative dimension of human experience, which is the possibility for reinvention and reconstruction of meanings. Finally, we present that it is possible to think about cultivation as a Bildung over ruins, one that recognizes the ruins not only as the negative of the unstoppable faith in historical progress but also of the closed impetus of development and cultivation. The child emerges as the one who is able to narrate, to create and to play in the rubbles of culture, which is one of the ways, for Benjamin, of being faithful to the possibility of emancipation.